2017
DOI: 10.4103/nmj.nmj_124_17
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic factors affecting the quality of life of elderly persons attending the general outpatient clinics of a tertiary hospital, South-South Nigeria

Abstract: Background: In the last few decades, the evaluation of the quality of life (QoL) among older adults has become increasingly important in health as well as in social sciences. There has been growing emphasis on the need to understand what influences older people's QoL as it is argued to be of greater value than the traditional outcome measures, such as health status. Aim and Objective: The aim of this study was to determine the sociodemographic factors affecting the QoL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…In this study there was a significant relationship between duration of illness of < 5 years, sedentary life style, presence of co-morbidities, medium and low medication adherence, and poor quality of life. This is similar to the findings in various studies conducted both locally and internationally [20,37,42]. The presence of co-morbidities was the most significant predictor of poor QOL in this study.…”
Section: Discussionsupporting
confidence: 91%
“…In this study there was a significant relationship between duration of illness of < 5 years, sedentary life style, presence of co-morbidities, medium and low medication adherence, and poor quality of life. This is similar to the findings in various studies conducted both locally and internationally [20,37,42]. The presence of co-morbidities was the most significant predictor of poor QOL in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Population living in suboptimal congested and unhygienic conditions are at a higher risk of fungal infections. Both quality of life as well as financial burden of the disease are highly dependent on the sociodemographic profile of patients (20) and cannot be stated to be only dependent on the disease and its severity hence sociodemographic profile is important in assessment of quality of life…”
Section: Impact On Financial Burdenmentioning
confidence: 99%
“…Furthermore, quality of life as a psychological construct explains the perception of an individual's position in life within the cultural context and value system in relation to goals, social relations, and expectations of the World Health Organization (WHO) (24). In a study by Morgan et al (25), it was indicated that good quality of life is an indicator of successful aging which enables individuals to adapt well in later life. In addition, Akinyemi et al (26) found that the adults living in suburban communities in Nigeria have a good quality of life.…”
Section: Introductionmentioning
confidence: 99%